Reference-Plane Invariant Free Space Dielectric Material Characterization up to 330 GHz. - Moreno-Rodríguez, Salvador; Pérez-Escribano, Mario; Ortiz Ruiz, Sergio; Alex-Amor, Antonio; Plaza-Gallardo, Borja; García-Ruiz, Francisco J.; Molero, Carlos (My University, 2024)
This paper describes the process followed to implement a system to characterize the complex permittivity of materials in the 10-330 GHz frequency band. Firstly, the method used and the system's calibration process are shown, consisting of a double calibration TRL (Thru-Reflect-Line) and GRL (Gated-Reflect-Line). Subsequently, a smoothing technique is used to improve the accuracy of the results. Finally, a test is performed on quartz and glass fiber samples, showing that the results are quite reliable over the entire measured bandwidth.
Keywords: Relajación dieléctrica; Materiales; Material; Characterization